Kontribusi PTKIN dalam Percaturan Politik Pendidikan Islam dan Sistem Pendidikan Nasional - Wardi, Moh. (Proceedings of Annual Conference for Muslim Scholars, 2019)
This paper discusses the contribution of PTKIN in the National Education arena, historically, the establishment of an Islamic College in Jakarta under the tutelage of K.H. Wahid Hasyim, Kahar Muzakkir and Bung Hatta. Likewise, the permissibility of ulama and nationalist leaders formed the ranks of the Defenders of the Motherland (PETA) and facilitated various activities of Muslims in the public and national sector. The entry of PTKIN cadres into the realm of bureaucracy such as the legislative body (Prof. Dr. KH Ali Maschan Moesa, M.Sc) Regional Representative Council (Prof. Dr. Hj. Istibjaroh, MA) Director General of Islamic Education Ministry of Religion of the Republic of Indonesia (Prof. Dr. Nur Syam, M.Sc) made a major contribution to institutional progress. Innovations and new ideas by strengthening institutions through the development of general study programs in order to meet the demands of the times, the flow of globalization and respond to the needs of the community with the orientation that with the opening of general study programs, there will be integration of science and religion which are inseparable intellectual heritage of Muslims. (worldly-ukhrawi harmonization).